Budgetary control in academic libraries - Martin, Murray S. (Greenwich, Conn. : Jai Press, 1978)
The most important contribution of the book is the recognition of economic hard times for libraries and the radical change this requires in the basic approach to the budgeting process.
Includes bibliographical references and index.
aia 03/04/2018
Loans
Keywords: Academic libraries $1 (BFinances; Academic libraries $1 (BAdministrations; Libraries, University and college $1 (BFinance.s; Libraries, University and college $1 (BAdministration.s